Molecular polymorphism: microwave spectra, equilibrium structures, and an astronomical investigation of the HNCS isomeric family. Issue 32 (1st August 2016) - McGuire, Brett A.; Martin-Drumel, Marie-Aline; Thorwirth, Sven; Brünken, Sandra; Lattanzi, Valerio; Neill, Justin L.; Spezzano, Silvia; Yu, Zhenhong; Zaleski, Daniel P.; Remijan, Anthony J.; Pate, Brooks H.; McCarthy, Michael C.
Abstract : The rotational spectra of four isomers of the [H, S, C, N] isomeric family are obtained by FTMW spectroscopy, enabling an astronomical search for these species. Abstract : The rotational spectra of thioisocyanic acid (HNCS), and its three energetic isomers (HSCN, HCNS, and HSNC) have been observed at high spectral resolution by a combination of chirped-pulse and Fabry–Pérot Fourier-transform microwave spectroscopy between 6 and 40 GHz in a pulsed-jet discharge expansion. Two isomers, thiofulminic acid (HCNS) and isothiofulminic acid (HSNC), calculated here to be 35–37 kcal mol −1 less stable than the ground state isomer HNCS, have been detected for the first time. Precise rotational, centrifugal distortion, and nitrogen hyperfine coupling constants have been determined for the normal and rare isotopic species of both molecules; all are in good agreement with theoretical predictions obtained at the coupled cluster level of theory. On the basis of isotopic spectroscopy, precise molecular structures have been derived for all four isomers by correcting experimental rotational constants for the effects of rotation–vibration interaction calculated theoretically. Formation and isomerization pathways have also been investigated; the high abundance of HSCN relative to ground state HNCS, and the detection of strong lines of SH using CH3 CN and H2 S, suggest that HSCN is preferentially produced by the radical–radical reaction HS + CN. A radio astronomical search for HSCN and its isomers has been undertaken toward the high-mass star-forming region Sgr B2(N) in the Galactic Center with the 100 m Green Bank Telescope. While we find clear evidence for HSCN, only a tentative detection of HNCS is proposed, and there is no indication of HCNS or HSNC at the same rms noise level. HSCN, and tentatively HNCS, displays clear deviations from a single-excitation temperature model, suggesting weak masing may be occurring in some transitions in this source.